2019
DOI: 10.1038/s41598-019-47890-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, prevalence, and outcome of primary biliary cholangitis in a nationwide Swedish population-based cohort

Abstract: Available epidemiological data on primary biliary cholangitis (PBC) in Sweden originate from regional studies in the 1980s and may not reflect modern day PBC. We aimed to estimate incidence and prevalence, survival and death causes, and gender differences in PBC. We used international classification of disease (ICD) codes to identify patients with PBC in inpatient and outpatient registries 1987–2014 who were then linked to the Swedish cause of death, cancer and prescribed drug registries. Each PBC patient was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 30 publications
(56 reference statements)
2
32
1
Order By: Relevance
“…For PBC, the high concordant association of about 10 was in line with the population-based Icelandic data [15]. AH and PBC showed shared familial associations with each other, the SIRs being 2.21 and 2.47, which is in line with polyautoimmunity between these AIDs [5]. AH and PBC shared any significant bidirectional associations with 10 other AIDs, most of which were lower than those between AH and PBC, suggesting that the two liver AIDs share somewhat more with each other than with extrahepatic AIDs.…”
Section: Plos Onesupporting
confidence: 82%
See 3 more Smart Citations
“…For PBC, the high concordant association of about 10 was in line with the population-based Icelandic data [15]. AH and PBC showed shared familial associations with each other, the SIRs being 2.21 and 2.47, which is in line with polyautoimmunity between these AIDs [5]. AH and PBC shared any significant bidirectional associations with 10 other AIDs, most of which were lower than those between AH and PBC, suggesting that the two liver AIDs share somewhat more with each other than with extrahepatic AIDs.…”
Section: Plos Onesupporting
confidence: 82%
“…Another limitation is that we have no information on co-morbidities in the study population because only the first AID was considered for each person to simplify the family study. However, the previous Swedish studies on AH and PBC report such data and the population in the PBC study is overlapping with the present one [3,5]. A further weakness was the definition of spouses which was based on the first common child and would not tell which of the couples subsequently divorced.…”
Section: Plos Onementioning
confidence: 69%
See 2 more Smart Citations
“…7,16,19 Recently, a large population-based analysis of both inpatient and outpatient registries in Sweden found that the prevalence of PBC increased steadily from 5.0 to 34.6 per 100,000 persons from 1987 to 2014, respectively. 20 Data collected from an Italian cohort between 2014 to 2015 reported that the point-prevalence of PBC was 27.9 per 100,000 people in Italy. 21 In addition to the scarcity of large population-based studies, misdiagnoses and underreporting of patients may also contribute to the incidence and prevalence of PBC, as 5-10% of patients may be antimitochondrial antibody (AMA)negative.…”
Section: Geographic Clustersmentioning
confidence: 99%